Use of emergency contraceptive pill in India: boon or bane - Verma, Anjana; Mathur, Medha; Meena, Jitendra Kumar; Kabra, Mukesh; Choudhary, Suresh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
It has been almost fifteen years since emergency contraceptive pills (ECPs) have been made available over the counter in India. There have been concerns about the overuse/misuse of ECPs and probability to replace regular contraceptive methods. This article presents various facets of the use of emergency contraceptive pills in India and highlights the importance of potential research to prevent its misuse.